2022
DOI: 10.1111/aji.13551
|View full text |Cite
|
Sign up to set email alerts
|

Human forkhead box protein 3 gene variants associated with altered susceptibility to idiopathic recurrent pregnancy loss: A retrospective case‐control study

Abstract: Background The pathogenesis of recurrent pregnancy loss (RPL) is multifactorial and not completely elucidated. Dysregulated immunity was implicated with RPL, in which regulatory T cells (Tregs) are key. As Tregs development and function are regulated by forkhead box P3 (FOXP3) transcription factor, and as FOXP3 expression is genetically determined, a role for FOXP3 polymorphisms in RPL pathogenesis was suggested. Aim To investigate the association of rs2294021, rs2232365, rs3761548, and rs141704699 FOXP3 varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…Thus, this feature of FOXP3 may serve as a mechanism of maternal tolerance to semi-allograft embryos. This hypothesis proposing the role of Treg in RPL pathogenesis is supported by recent research findings, which suggest that FOXP3 gene variants and haplotypes could be associated with RPL [33,132].…”
Section: Immune Factorssupporting
confidence: 65%
See 1 more Smart Citation
“…Thus, this feature of FOXP3 may serve as a mechanism of maternal tolerance to semi-allograft embryos. This hypothesis proposing the role of Treg in RPL pathogenesis is supported by recent research findings, which suggest that FOXP3 gene variants and haplotypes could be associated with RPL [33,132].…”
Section: Immune Factorssupporting
confidence: 65%
“…Recently the role of forkhead 3 box protein (FOXP3) in RPL was proposed [ 33 , 131 , 132 ]. FOXP3 is a nuclear transcription factor required to induce immunosuppressive activity [ 131 , 133 ].…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, many researchers have reported that women with URPL have lower Tregs levels than normal patients ( 24 , 25 ). Up to now, numerous results generally suggest that lower Tregs level is associated with a higher risk of miscarriage in women with URPL ( 12 , 13 , 26 ). However, our study revealed for the first time that either lower or higher Tregs levels increase the risk of miscarriage in women with URPL.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the precise pathophysiological mechanisms behind PCOS have yet to be fully elucidated. Genetic differences have been identified as a contributing factor to the pathophysiology of PCOS in many investigations [3,4]. Furthermore, it has been shown that there is a correlation between insulin resistance and the pathophysiology of PCOS [5,6].…”
Section: Introductionmentioning
confidence: 99%